1
$\begingroup$

I was doing some exercises about alternate series and at some of them i could show that that the series was not absolutely convergent, since the term $a_n \not\rightarrow 0$ as $n \rightarrow \infty$ .

So i came up with the question: is $\lim a_n = 0$ also a necessary condition for the convergence of the alternating series $\sum (-1)^na_n?$

Here's my anwser:

Suppose that $\sum (-1)^na_n$ has a finite sum $s$. Let $s_n=a_1-a_2+...+(-1)^{n-1}a_n $ be the sequence of the partial sums. We have that $\lim s_n = s$ and also that $\lim s_{n-1} = s$, since $(s_{n-1})$ is a subsequence of $(s_n)$ . Therefore,

$$ 0 = s-s = \lim s_n - \lim s_{n-1} = \lim (s_n - s_{n-1}) = \lim(-1)^{n-1}a_n$$

and this shows that $\lim a_n = 0$, since both even and odd subsequences of $b_n = (-1)^{n-1}a_n$ goes to the same limit: $0$.

Is it right?

$\endgroup$
  • 4
    $\begingroup$ The condition $\lim_{n\to\infty} a_n = 0$ is a necessary condition for the convergence of any infinite series. It's called the "$n$-th term test (for divergence)" (i.e., if it fails, the series diverges). See:$\;$en.wikipedia.org/wiki/Term_test $\endgroup$ – quasi May 17 '17 at 18:31
0
$\begingroup$

Looks good - the only thing I was wary of was this statement: $\lim a_n - \lim b_n = \lim(a_n-b_n)$

But it looks like it is true if $\lim a_n=\lim b_n:=a$ exists.

Because: $$\forall\varepsilon>0\quad \exists N\in\mathbb{N}: |a_n-a|<\varepsilon\quad \forall n\ge N$$ then:

$$|a_n-b_n|=|a_n-a+a-b_n|\le|a_n-a|+|a-b_n|<\frac{\varepsilon}{2}+\frac{\varepsilon}{2}=\varepsilon\quad \forall n\ge N$$

So $\lim(a_n-b_n)=0$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.